Upaya Masyarakat Dalam Membentuk Lingkungan Bersih Dan Implikasinya Dalam Pelaksanaan Pendidikan Islam Anak Di Desa Manyarejo Kecamatan Manyar Kabupaten Gresik. - Nur Khamim; Andi Asyhari (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
Maintaining cleanliness is an obligation in order to realize the benefits and prevent the occurrence of disrespect. The goal is for man to carry out his duties as a servant as well as the caliph of God on the earth well. This article will discuss about the efforts of the community to create a clean environment and its implications for the implementation of Islamic Education which is the result of research that has been conducted in manyarrejo village. The research method that researchers use in this study is a descriptive type of research with qualitative approach. Community efforts in forming a clean environment in manyarejo village by holding devotional work, not littering, reforestation. In addition, greening by utilizing narrow land, changing people's lifestyles and following waste banks. The religious climate in the environment in Islamic educational institutions can be realized through: Theexistence of learning methods by using the approach of religious values in everylearning, especially environmentally based religious values to childern can be tucked into verses related to the environment. As well as theexistence of examples of educators who have noble morals, especially have concern for the environment such as providing education to students to dispose of waste in its place